MURAL DAN DESAIN LOGO SARI KEDELAI & SUSHI - Yuliaty, Erma; Prihastuty, Dyah Rini (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
This article contains the creation of mural and food products design made by KWU division. The purpose of this article is to improve product quality on the design of KWU division product output. This research is done by method. From this article can be concluded people interested in making sushi and soymilk products. So, the design created by KWU division is beneficial to improve products managed by the community.